Chimeras: Inventory of Synthetic Cognition - Manouach, Ilan -1980; Engelhardt, Anna -1994 (Onassis Foundation, 2022)
This volume attempts to disassemble and reformulate what one might understand as AI by taking apart both notions of 'artificiality' and 'intelligence' and seeing what new meaning they produce when recombined.We summon the trickster of the natural order, chimera, both a mythical creature and a genetic phenomenon. Drawing upon chimerism allows us to broaden 'artificial intelligence' into 'synthetic cognition'⁠—an approach that highlights the duality of 'artificial' and 'authentic', amplifies non-human methods of cognition and anticipates modes of symbiosis.With this aim, the editors, Ilan Manouach and Anna Engelhardt, assembled an inventory in which one can find contributions from scholars and artists with interspecies, disability, monstrous, feminist, and decolonial approaches, as well as thinkers and technologists engaged in a broader field of AI. By questioning fabricated norms that constitute and maintain notions of 'artificial' and 'intelligence', this inventory acts as a toolbox one can use to merge these terms into a novel chimera.
Keywords: Artificial intelligence; Technology; Artistic research